Answer: The correct option is
(B) [tex]T^{-1}(x,y)=(x-3,y+2).[/tex]
Step-by-step explanation: Given that under T, the point (0,2) gets mapped to (3,0).
We are to find the expression for [tex]T^{-1}(x,y).[/tex]
According to the given information, we have
[tex]T(0,2)=(3,0)=(0+3,2-2)\\\\\Rightarrow T(x,y)=(x+3,y-2)\\\\\Rightarrow T^{-1}(x+3,y-2)=(x,y)\\\\\Rightarrow T^{-1}(x+3-3,y-2+2)=(x-3,y+2)\\\\\Rightarrow T^{-1}(x,y)=(x-3,y+2).[/tex]
Thus, the required expression is [tex]T^{-1}(x,y)=(x-3,y+2).[/tex]
Option (B) is CORRECT.